THE EMERGENCE OF PROBABILISTIC LANGUAGE FROM STUDENTSâ UNCERTAINTY IN LEARNING INFORMAL INFERENTIAL REASONING - Fakhmi, Lukman; Windri, Heninga; Meitriana Manurung, Mika (EDU-MAT, 2017)
In our daily life, we often draw conclusion regarding some phenomenon to get new information from sampleof the population. By doing so, we unconsciously learn the inferential statistics informally or known as Informal Inferential Reasoning (IIR). Therefore, it can be said that IIR is close to our live. As a result, it is wise to use IIR in introducing inferential statistics to students. In introducing IIR, a set of learning design needs to be made. In this research, the design would use Realistic Mathematics Education (RME) as the approach of the learning and dot plot as a visual representation. This paper describes the probabilistic language students used in expressing some uncertainty when making generalization. The method used is design research. The involved subjects in this research were six students of VII-8 at SMPN 7 Tangerang Selatan. The results showed that the probabilistic language appears when students generalize the data. Moreover, probabilistic language also appears when students added samples in growing sample activity. Probablistic language which appeared in this research are âmungkinâ, âhampir samaâ, âkurang samaâ, and so on.Â Keywords : design research; informal inferential reasoning; probabilistic language; uncertainty.